2018
DOI: 10.14742/ajet.2989
|View full text |Cite
|
Sign up to set email alerts
|

Australian university students’ access to web-based lecture recordings and the relationship with lecture attendance and academic performance

Abstract: Web-based lecture technology (WBLT) allows students access to recorded lectures delivered live to the classroom any time and to any device with internet. This technology has become standard across universities. This study of Australian undergraduate psychology students explored many important questions related to WBLT. About 75% of students surveyed utilised recorded lectures. Qualitative responses allowed students to explain many reasons for using WBLT, including to study for exams, regular study throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…This is in agreement with the results of the meta-analysis of Allen et al (2004) which indicated that the use of synchronous interactive technology does not necessarily mean increased final grades. This is also similar to previous research that found no difference in final grades when comparing different patterns of attending face-to-face lectures and accessing recordings of the lectures (Chapin, 2018;Kinash, Knight, & McLean, 2015). This may be due to vicarious interaction when students learn from watching other students interact (Sutton, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the results of the meta-analysis of Allen et al (2004) which indicated that the use of synchronous interactive technology does not necessarily mean increased final grades. This is also similar to previous research that found no difference in final grades when comparing different patterns of attending face-to-face lectures and accessing recordings of the lectures (Chapin, 2018;Kinash, Knight, & McLean, 2015). This may be due to vicarious interaction when students learn from watching other students interact (Sutton, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…The literature shows a variation in the uptake of recorded lectures; disciplines such as business, the social sciences and the engineering exhibit more positive attitude towards the use of lecture recording compared to lecturers in the science disciplines (Dona et al 2017 ; Rahman et al 2018 ). Chapin ( 2018 ) identified four types of students who engage with lecture recording: Students who attended lectures regularly and did not access the lecture recordings; Those who regularly attended lectures and used lecture recordings to reinforce what they had learned in class, and for exams; Those who attended lectures and only accessed the recordings when they had missed a lecture, wanted to reinforce what they learned and prepare for exams; Those did not attend lectures either by choice or circumstances and relied on the recordings. …”
Section: Introduction and Related Researchmentioning
confidence: 99%
“…Among the handful of articles that included such a level of details, length of the lectures captured was mostly reported as 1 h or less (e.g., Brooks et al, 2014 ; Elliott & Neal, 2016 ; Williams et al, 2016 ). In three articles, duration of the lectures varied from one to 2 h ( Chapin, 2018 ; Jones & Olczak, 2016 ; Trenholm et al, 2019 ). In yet another three articles, lectures were as long as 3 h ( Bollmeier et al, 2010 ; Chen & Lin, 2012 ; Owston et al, 2011 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Drouin (2014) further revealed that even though students had a positive attitude toward lecture capture, they seldom viewed the actual lecture recordings. In addition, despite the general proclivity of the scholarly community to report only significant results and under-report those that are non-significant ( Kerr, 1998 ; Yukhymenko, 2011 ), it is telling that several works have indicated a non-significant association between lecture capture viewing and academic performance ( Bollmeier et al, 2010 ; Chapin, 2018 ; Euzent et al, 2011 ; Ford et al, 2012 ; Hadgu et al, 2016 ; Leadbeater et al, 2013 ; Mallinson & Baumann, 2015 ; Sarsfield & Conway, 2018 ; Traphagan et al, 2010 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation